Porky Pig : 101 classic Warner Bros animated shorts. (Archive collection., 2017)
"That's NOT all, folks! Warner Bros. first cartoon superstar, everyone's favorite pantless porcine, Porky Pig, takes center stage. From his humble beginnings as the breakout star of a schoolhouse talent show in I haven't got a hat to his slimmer, slaphappy sidekick stage alongside Daffy Duck in Porky Pig's feat, across Merrie Melodies and Looney Tunes, in two-strip Technicolor® and scintillating black and white, Porky's ascent from rascally school gang member to superstar spokespig is fully on display in the 5-disc, 101-cartoon (plus some bonuses) collection. Presented in chronological order, with key commentaries by noted animation scholars and superfans on select shorts of significance, this tome contains all the 'toons you need to become a true professor of Porky Pig-ology."--Container insert.